THE ROLE OF GENETIC DETERMINANTS AND DISORDERS IN SYSTEMIC AND LOCAL IMMUNITY IN THE ETIOLOGY AND PATHOGENESIS OF HERPETIC ECZEMA (KAPOSI'S ECZEMA) - A. S. Stadnikova; O. B Tamrazova; T. A. Chebotareva (Детские инфекции (Москва))
This review presents an analysis of the literature data on the etiology and pathogenesis  of Herpetic Eczema (Kaposi's Eczema). Modern views on the complex genetic and phenotypic determinants of disease, reflecting the complex interactions between the skin and the immune system. Along with the general regularities characteristic of Herpetic Eczema in sufficient detail the reasons of infringements of functioning of the epidermal skin barrier, which contribute to an easier penetration of the Herpes Simplex  Virus in the skin and its binding  to cellular receptors in the implementation of the infectious process. The effect of systemic and local immunity, namely, changes in T-cell and interferon system in the development of the pathological process.